The Influence of Tax Sanctions and Service Quality on Compliance with Paying Motor Vehicle Taxes among STIE EKA Prasetya Management Department Students Semester VIII - Muammar Rinaldi; Putri Wahyuni (Outline Journal of Management and Accounting, 2023)
This research aims to know the effect of Tax Sanction and Service Quality against Compliance of Vehicle Tax Payment partially and simultenously on STIE Eka Prasetya Students Majoring in Management 8th Semester. The population for this research are STIE Eka Prasetya 8th Semester students which is 153 students. The sampling technique used in this research is purposive sampling. By using purposive sampling, a total of 64 students is chosen. The results of the research analysis showed that Tax Sanction and Service Quality has a significant effect on Compliance of Vehicle Tax Payment. F test shows that Tax Sanction and Service Quality has a significant effect on Compliance of Vehicle Tax Payment. The result of determination coefficient (R Square) shows that Compliance of Vehicle Tax payment can be explained by Tax Sanction and Service Quality. As of the remaining can be explained by other variable which is not included on this research such as Tax Knowledge, Taxpayer Awareness, and Taxation Socialization.